The Use of Social Media on Self-Concept in Adolescents: A Multiple Case Study - Purnama, Heni; Fitriana, Anisa Nur (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: Adolescent self-concept plays a role so that adolescents can adjust to their environment, adolescent self-concept can be influenced by the use of social media. Social media can have a positive or negative influence on adolescent self-concept. Method: A qualitative research methodology was utilized with multiple case study design. Data collection using structure interview. The subjects in this study were 2 teenagers who active using social media. This research was conducted in the Bandung area. Results: Teenagers use social media to express honesty, share photos, and share daily lives. However, excessive use negatively impacts self-concept, productivity, and empathy, leading to distractions like forgetting study time and helping parents clean. Conclusion: Social media can affect self-concept in adolescents depending on the use made by adolescents, on social media adolescents get a negative or positive self-concept.